Tanzania manufacturing sector in response to trade liberalization: A case of pharmaceutical manufacturing - Gesoreka, George (Mzumbe University, 2026)
A dissertation submitted to the Dar es Salaam Campus College in partial fulfilment of the requirements for the award of the Master of Business Administration (MBA) degree of Mzumbe University